Roles of animals and eco-psychology in the healing of trauma in contemporary fiction - Khandhar, Diren Ashok (2021)
The field of Eco-Psychology is an emerging avenue to help understand better the effectiveness of human-nature bond in the recovery and healing of psychological trauma. The capacity to live in balance with nature has been identified as the key element to improve the spiritual and emotional well-being of humans by creating a reciprocal relationship between humans and the natural world surrounding them. In order to achieve this unification, the awakening of ecological unconscious in human minds is fundamental as this would be the key element to be tapped into for humans to realize the true powers nature possesses. One of the most notable connections man has with nature is through animals and this association has been characterised to facilitate therapy for humans through the diverse inherent qualities that animals possess. These qualities are worth to be explored in ascertaining better how trauma can be negotiated with the intervention of animals. Herein, this thesis firstly aims to analyse the varied manifestations of trauma in the selected literary texts using the trauma model by Cathy Caruth as well as other Trauma theorists. The next objective that is aimed to be accomplished is to examine the awakening of ecological unconscious among the selected literary characters using the theory of Eco-psychology by Theodore Roszak and Andy Fisher. Once this has been achieved, the relationship between human and animals is investigated further to ascertain how this union is fundamental in aiding to heal psychological trauma in the literary characters of the novels selected for this thesis. The three literary texts that have been selected as the primary sources for this include Suspect (2013) by Robert Crais, Archipelago (2012) by Monique Roffey, and Life of Pi (2001) by Yann Martel. These novels are deliberately chosen as they contain elements pertaining to psychological trauma that have stemmed from natural disasters, murder and personal tragedy. All these catastrophes ultimately led the characters in the fiction to experience different exhibits of trauma such as hallucinations, extreme anxiety, flashbacks and nightmares. Mode of recovery started to transpire when these characters begun to establish a deep affiliation with the natural world surrounding them. The non-human natural world played an integral role in the integration of psyches between the literary characters and the environment surrounding them as well as helped in the process of recovery of psychological trauma through their observations and assimilation with the animal characters.